SENYAWA KIMIA AKTIF BUAH NIPAH (Nypa fruticans Wurmb) BERDASARKAN 3 TINGKAT KEMATANGAN BUAH - Elmalia Rinten Suryanizak; Rosidah Radam; Yuniarti Yuniarti (Jurnal Sylva Scienteae, 2023)
The nipah plant (Nypa fruticans Wurmb) is a type of betel nut tribe that lives in brackish water marsh areas. The spread of nipah in South Kalimantan covers areas in Banjar Regency, Tanah Laut Regency, Tanah Bumbu Regency and Pulau Laut Regency. Nipah fruit has antibacterial content and is useful as a food source that can be used as a diet food. This study aims to analyze the content of akif chemical compounds, namely flavonoids, tannins, alkaloids, steroids and triterpenoids in nipah fruit (Nypa fruticans Wurmb) at 3 levels of fruit maturity. Phytochemical tests are carried out to determine the class of compounds contained in nipah fruit. This research began with the manufacture of simplicia first then a phytochemical test was carried out using a color test, showing positive results that the nipah fruit contains active chemical compounds alkaloids and tanninsTumbuhan nipah (Nypa fruticans Wurmb) merupakan jenis palem atau suku pinang-pinangan yang hidup di daerah rawa berair payau. Penyebaran nipah di Kalimantan Selatan meliputi wilayah di Kabupaten Banjar, Kabupaten Tanah Laut, Kabupaten Tanah Bumbu dan Kabupaten Pulau Laut. Buah nipah memiliki kandungan antibakteri dan bermanfaat sebagai sumber pangan yang dapat dijadikan sebagai makanan diet. Penelitian ini bertujuan menganalisis kandungan senyawa kimia akif yaitu flavonoid, tanin, alkaloid, steroid dan triterpenoid pada buah nipah (Nypa fruticans Wurmb) pada 3 tingkat kematangan buah. Uji fitokimia dilakukan untuk mengetahui golongan senyawa yang terdapat dalam buah nipah. Penelitian ini diawali dengan pembuatan simplisia terlebih dahulu kemudian dilakukan uji fitokimia menggunakan tes uji warna, menunjukkan hasil positif bahwa buah nipah mengandung senyawa kimia aktif alkaloid dan tanin.